1999
DOI: 10.1002/(sici)1097-4644(19991201)75:3<492::aid-jcb13>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3, αvβ5, and osteopontin are coordinately upregulated at early time points in a rabbit model of neointima formation

Abstract: Both smooth muscle cell migration and replication are known to be responsible for neointima formation. Recent reports based on in vitro studies and animal models of neointima formation highlight the possible importance of alphavbeta3 and alphavbeta5 integrins in mediating neointima formation. Clinical data suggest that specific alphavbeta3 blockade may limit restenosis. The aim of this study was to identify the expression of alphavbeta3 and alphavbeta5 and their ligand osteopontin in the very early phases of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Several studies have shown that a variety of cell types utilize Shc activation in response to IGF-I to signal to MAP kinase (3,5,6,9,15,36,37,49,50), and in some cell types IRS-1-mediated signaling has been shown to be down-regulated in response to stress or changes in nutrient availability (51,52). However, the frequency with which this pathway is activated selectively during normal growth in vivo or whether its role is limited to pathophysiologic states such as following vascular injury has not been determined (53).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a variety of cell types utilize Shc activation in response to IGF-I to signal to MAP kinase (3,5,6,9,15,36,37,49,50), and in some cell types IRS-1-mediated signaling has been shown to be down-regulated in response to stress or changes in nutrient availability (51,52). However, the frequency with which this pathway is activated selectively during normal growth in vivo or whether its role is limited to pathophysiologic states such as following vascular injury has not been determined (53).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Tyr 261 and the Asp 172 correspond to a heparin binding site and a phosphorylation site overlapped by the homologous Itga 4 b 1 binding site of fibronectin, respectively [15]. Asn 126 neighbors the RGDS motif that serves as a binding site for Itga v b 1 [36], a v b 3 [37], and a v b 5 [38]. The critical substitutions for the functional differences of allelic OPNs need to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the intervention, an early inflammatory response characterized by the recruitment and adhesion of leucocytes, macrophages, and activated platelets to the site of the vessel injury can be observed. In addition to various growth factors and cytokines released locally by resident and recruited cells, plasma proteins such as vitronectin, osteopontin, and fibronectin are deposited at the site of the lesion [4][5][6][7]. A combination of these chemotactic and haptotactic stimuli drives the proliferation and migration of vascular cells, mainly smooth muscle cells (SMCs), leading to their accumulation in the newly formed neointima.…”
mentioning
confidence: 99%